2016
DOI: 10.1111/ina.12322
|View full text |Cite
|
Sign up to set email alerts
|

External eye symptoms in indoor environments

Abstract: Eye irritation, for example dry or irritated eyes, is generally among top three reported symptoms in office-like environments, in particular among workplaces with cognitive demanding visual display unit (VDU) work. The symptoms are especially among middle and advanced ages and particularly among women more than men. The symptoms are also among the most commonly reported complaints in the eye clinic. To be in a position to interpret the high prevalence of eye symptoms, a multidisciplinary and integrated approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 246 publications
(315 reference statements)
5
55
0
8
Order By: Relevance
“…Long‐term exposure to the most common air pollutants, for example, NO 2 , aldehydes, VOCs, particulate matter (PM), even at low concentrations, may affect human health, causing or aggravating diseases such as allergic and asthma symptoms, lung cancer, chronic obstructive pulmonary disease, sensory irritation, and cardiovascular diseases . In addition, correlations, that is, single dose‐response relationships, between common indoor air pollutant (IAP) concentrations and self‐reported symptoms and complaints have not been found suggesting the multifactorial causality of symptoms and that a given symptom may arise from a combination of individual, occupational, and environmental risk factors . On the other hand, some relations have been found between building characteristics or user patterns and self‐reported health complaints .…”
Section: Introductionmentioning
confidence: 99%
“…Long‐term exposure to the most common air pollutants, for example, NO 2 , aldehydes, VOCs, particulate matter (PM), even at low concentrations, may affect human health, causing or aggravating diseases such as allergic and asthma symptoms, lung cancer, chronic obstructive pulmonary disease, sensory irritation, and cardiovascular diseases . In addition, correlations, that is, single dose‐response relationships, between common indoor air pollutant (IAP) concentrations and self‐reported symptoms and complaints have not been found suggesting the multifactorial causality of symptoms and that a given symptom may arise from a combination of individual, occupational, and environmental risk factors . On the other hand, some relations have been found between building characteristics or user patterns and self‐reported health complaints .…”
Section: Introductionmentioning
confidence: 99%
“…In this study of four well‐functioning office buildings, the indoor environment was generally were well controlled. This caused small variation in many IEQ factors, thus limiting the ability to observe significant links between some IEQ factors and physiological outcomes that might be found in other research …”
Section: Limitationsmentioning
confidence: 96%
“…Policymakers, standards developers, and building design and operations professionals are increasingly interested in indoor environment quality (IEQ) and its effect on occupant health and comfort. Despite several studies revealing the potential negative impact of both too high and too low relative humidity (RH) on health and comfort, the importance of controlling RH has received less attention than other IEQ parameters and lower limits have been removed from thermal comfort standards.…”
Section: Introductionmentioning
confidence: 99%
“…Intact skin poses an effective barrier against the absorption of particles, but the thin epidermal layers of mucosal surfaces are less protective. Epidemiologic studies have reported that burning, dryness, and itching of the eyes are among the most common symptoms from occupant complaints . Prolonged exposure to environmental particulate pollution can cause severe disease .…”
Section: Introductionmentioning
confidence: 99%